Muscle and tendon stiffness and belly gearing positively correlate with rate of torque development during explosive fixed end contractions. (4th January 2021) - Monte, Andrea; Zignoli, Andrea
Abstract: We combined ultrafast-ultrasound with dynamometric measurements to assess the associations between muscle structural properties and the rate of torque development (RTD) during isometric explosive fixed-end plantar flexor contractions. The torque-time signal was recorded for the plantaflexor muscles in fifteen men and the peak value of RTD was obtained. Tendon stiffness (kT) and muscle stiffness (kM) of the Gastrocnemius Medialis (GM) were assessed during maximal isometric voluntary contractions (MVC) and quick release using ultrafast ultrasound (1000 Hz). During the explosive contraction, the GM geometrical changes were recorded and the belly gearing (belly velocity/fascicle velocity) was calculated. Pearson's correlation coefficient was used to assess the correlation between variables, whereas equality of correlation coefficients between RTD and kT and kM was tested by means of the Hotelling's statistics. During explosive contraction, kT was higher than kM (~55 and ~30 N⋅mm − 1, respectively). RTD positively correlated with kM (r = 0.75, p < 0.001), kT (r = 0.58, p = 0.044) and belly gearing (r = 0.78, p < 0.001). However, Hotelling's test showed no significant differences between the correlation coefficients between RTD and muscle and tendon stiffness. Further, belly gearing was significantly positively correlated with kM only (r = 0.79, p < 0.001). Our data suggest that muscle and tendon stiffness are similarly associated with RTD. Given the association with belly gearing, muscle stiffness seems to play an important role in determining the muscle length changes, thereby affecting the muscle force transmission capacity during the transient phases.